Hubungan Faktor Risiko Karies Gigi terhadap Kualitas Hidup Lansia di Kabupaten Jember - Zahreni Hamzah; Amandia Dewi Permana Shita; Ari Tri Wanodyo Handayani; Dyah Indartin Setyowati; Asyifa Af Ida Haffiz (Fakultas Kedokteran Gigi Universitas Jember, 2023)
When aging, elderly people are expected to have a good quality of life. However, the elderly are vulnerable to various dental and oral health problems such as dental caries. The impact of tooth decay affects the quality of life of the elderly regarding oral health (Oral Health Related Quality of Life). The aim of this research is to determine the relationship between risk factors for dental caries and the quality of life of the elderly in Jember district. This research was conducted from January to March 2022 in three sub-districts in Jember Regency. The total number of respondents required is 168, who are classified into the pre-elderly group (45-59 years) and the elderly group (≥60 years). The instrument used in this research was a questionnaire. Risk of dental caries using a questionnaire based on CAMBRA (Caries Management by Risk Assessment) and Quality of life related to dental health using the OHIP-14 questionnaire. The data analysis method used was statistical analysis using the Spearmen non-parametric correlation test; with a significance level of 0.01. Spearman correlation analysis shows a high correlation indicated by a figure of -0.580(**), which means it falls into the range 0.51–0.75 which is defined as having a strong relationship in the negative direction. The higher the risk factors for caries in the elderly in Jember district, the lower their quality of life.